Protective Effects of Obstructive Sleep Apnea on Outcomes After Subarachnoid Hemorrhage: A Nationwide Analysis. Issue 5 (15th June 2020) - Kaculini, Christian; Wallace, David J; Haywood, Audrey E; Michalek, Joel; Mascitelli, Justin; Seifi, Ali; Grandhi, Ramesh
Abstract: BACKGROUND: Obstructive sleep apnea (OSA) is typically associated with an increased risk of cardiovascular and cerebrovascular disease. Recent studies, however, have suggested that hypercapnia and chronic intermittent hypoxia may potentially provide protection against ischemic events like stroke. OBJECTIVE: To evaluate the impact of OSA with presentation, hospital course, and treatment outcomes of patients with subarachnoid hemorrhage (SAH). METHODS: Data for patients with SAH between the years 2011 and 2015 were extracted from the Nationwide Inpatient Sample (NIS) and stratified based on diagnosis codes for OSA. Univariate analysis was used to assess the prevalence of comorbidities in OSA patients diagnosed with SAH and several covariates, including patient demographics, aneurysmal treatment, in-hospital morality rate, length of stay, and costs. Multivariate logistic regression models analyzed the relationship between several comorbidities, including OSA, tobacco use, and hypertension, and poor outcomes after SAH. RESULTS: Data from 49 265 SAH patients were used in this study, of which 2408 (4.9%) also had a concomitant OSA diagnosis. Patients with OSA compared to all other SAH patients had a significantly lower in-hospital mortality rate, as well as statistically significant lower odds of vasospasm, stroke, and poor outcomes. Additionally, hypercholesterolemia, obesity, and tobacco use disorder were also associated with more favorable outcomes. CONCLUSION: SAH patients with OSA are significantly less likely to have a poor outcome when compared to non-OSA patients, despite having an increased risk of several comorbidities.